Efektivitas Metode Eksperimen Terhadap Minat Belajar Siswa pada Pelajaran IPA pada Siswa Kelas IV SD Tri Dharma Sei Semayang - Idiawati, Budi; Ramadhani, Mastari; Harahap, Syarifah Ainun (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This research employs a descriptive qualitative method, aiming to reveal the actual influence of school facilities and infrastructure on enhancing the learning motivation of grade V students at UPT SPF SD Negeri 104202 Bandar Setia, Percut Sei Tuan, Deli Serdang. The study involved 30 students as experimental units and was conducted over six meetings. The research focuses on the availability of standard educational facilities, such as classrooms, sports venues, libraries, laboratories, and other learning resources, including the use of information and communication technology, which support the learning process. The hypothesis testing results show a calculated r value (r_count) of 0.484, which is greater than the r value from the distribution table (r_table = 0.361) at a significance level of 5%, indicating that H1 is accepted. This confirms that there is a significant influence of school facilities and infrastructure on improving the learning motivation of the students.